Prognostic significance of systemic immune inflammation index for ovarian cancer: An updated systematic review and meta-analysis - Boliang Chu; Yingying Chen; Jiewei Pan (Journal of Ovarian Research)
Abstract Objective Several inflammatory indices have been used to assess the prognosis of ovarian cancer, with variable results. This review assessed whether the systemic immune inflammation index (SII) can predict outcomes in patients with ovarian cancer. Methods Embase, PubMed, CENTRAL, Web of Science, and Scopus databases were searched by the two reviewers from inception to 15th October 2024 for studies assessing the relationship between SII and overall survival (OS) or disease-free survival (DFS). Results Ten studies with eleven cohorts were included. Pooled analysis showed that higher SII was a significant predictor of poor OS (HR: 2.35 95% CI: 1.56, 3.55 I2 = 88%) and worse DFS (HR: 2.51 95% CI: 1.71, 3.67 I2 = 80%) after ovarian cancer. Sensitivity analysis failed to change the significance of the results. No publication bias was noted. Most results remained significant on subgroup analyses based on location, sample size, FIGO stage, treatment, adjusted outcomes, cut-off of SII, method of determining cut-off, and quality score. Conclusions SII can be a potential predictor of OS and DFS after ovarian cancer. Further studies are required to improve the evidence.